Translating writings of early scholars in the ancient Near East, Egypt, Greece, and Rome : methodological aspects with examples - Imhausen, Annette; Pommerening, Tanja (Beiträge zur Altertumskunde., 2016)
Ancient cultures have left written evidence of a variety of scientific texts. But how can/should they be translated? Is it possible to use modern concepts (and terminology) in their translation and which consequences result from this practice? Scholars of various disciplines discuss the practice of translating ancient scientific texts and present examples of these texts and their translations.